Transcriptomic and metabolomic analysis provides insights into lignin biosynthesis and accumulation and differences in lodging resistance in hybrid wheat - Weibing Yang; Shengquan Zhang; Qiling Hou; Jiangang Gao; Hanxia Wang; Xianchao Chen; Xiangzheng Liao; Fengting Zhang; Changping Zhao; Zhilie Qin (Journal of Integrative Agriculture)
The use of hybrid wheat is one way to improve the yield in the future. However, greater plant heights increase lodging risk to some extent. In this study, two hybrid combinations with differences in lodging resistance were used to analyze the stem-related traits during the filling stage, and to investigate the mechanism of the difference in lodging resistance by analyzing lignin synthesis of the basal second internode (BSI). The stem-related traits such as the breaking strength, stem pole substantial degree (SPSD), and rind penetration strength (RPS), as well as the lignin content of the lodging-resistant combination (LRC), were significantly higher than those of the lodging-sensitive combination (LSC). The phenylpropanoid biosynthesis pathway was significantly and simultaneously enriched according to the transcriptomics and metabolomics analysis at the later filling stage. A total of 35 critical regulatory genes involved in the phenylpropanoid pathway were identified. Moreover, 42% of the identified genes were significantly and differentially expressed at the later grain-filling stage between the two combinations, among which more than 80% were strongly up-regulated at that stage in the LRC compared with LSC. On the contrary, the LRC displayed lower contents of lignin intermediate metabolites than the LSC. These results suggested that the key to the lodging resistance formation of LRC is largely the higher lignin synthesis at the later grain-filling stage. Finally, breeding strategies for synergistically improving plant height and lodging resistance of hybrid wheat were put forward by comparing the LRC with the conventional wheat applied in large areas.